2020
DOI: 10.4103/jfmpc.jfmpc_32_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiac output measured by carotid artery Doppler ultrasound and echocardiography in patients admitted to Golestan and Imam Khomeyni Hospitalsl in Ahvaz

Abstract: Introduction: Ultrasound is highly effective, safe, and cost-effective for monitoring the hemodynamics and measuring the cardiac output of patients. This study aims to investigate the value of cardiac output by the measurement of common carotid artery flow, which is an inexpensive, simple, and accessible method. Method: Doppler ultrasound of the carotid artery at thyroid level was obtained from the patients admitted to Golestan and Imam Khomeyni Hospitals in Ahvaz (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
0
0
Order By: Relevance
“…The authors suggested that the signi cant decrease in ICBF was related to the decrease in CO. In addition, a strong correlation of 0.96 close to 1 between ultrasonic measured CBF and TTE measured CO was reported by Fazelinejad [12].…”
Section: Discussionsupporting
confidence: 60%
“…The authors suggested that the signi cant decrease in ICBF was related to the decrease in CO. In addition, a strong correlation of 0.96 close to 1 between ultrasonic measured CBF and TTE measured CO was reported by Fazelinejad [12].…”
Section: Discussionsupporting
confidence: 60%
“…The authors suggested that the significant decrease in ICBF was related to the decrease in CO. In addition, a strong correlation of 0.96 (close to 1) between CBF measured by ultrasound and CO measured by TTE was reported by Fazelinejad et al [12].…”
Section: Resultssupporting
confidence: 54%